Title: Serious COVID-19 may have a causal relationship with myocardial injury: A Mendelian randomization study - Liu, Mei Jia; Sun, Xue Qing; Li, Long Bo; Wang, Guan; Shi, Yong Feng (Frontiers in Genetics, 2023)
Background: The association of coronavirus disease 2019 (COVID-19) with myocardial injury is not well known. This study explored the association between them using the Mendelian randomization (MR) method. Method: We obtained summary data from genome-wide association studies (GWAS) on myocardial injury and COVID-19 from public databases. Then, as tool variables, we chose single nucleotide polymorphisms associated with susceptibility and COVID-19 severity to investigate the causal relationship of COVID-19 with myocardial injury using inverse-variance weighting (IVW) as the primary approach. Finally, the reliability of the results was evaluated by performing sensitivity analyses. Results: As revealed by the IVW analyses, the seriously hospitalized patients with COVID-19 had causality with myocardial injury, with an βof 0.14 and 95% confidence interval (CI) of 0.03 – 0.25 (p = 0.01). The results showed that COVID-19 with severe respiratory symptoms positively affected myocardial injury (β = 0.11, 95% CI = 0.03 – 0.19; p = 0.005). Conclusions: According to this study, severe respiratory symptoms and hospitalization due to COVID-19 may increase the risk of myocardial injury.